Bio-archaeological analysis of a tooth from a human burial. Summit of Cerro Madre e Hija (Santa Cruz, Argentina) - Atencio, Juan Pablo; Magnin, Lucía; Blanco, Laura (Revista Chilena de Antropología, 2020)
As part of a current investigation a number of stone structures have been registered throughout the locality of Santa Cruz (Argentina), which have been assigned to various functions such as hunting blinds, cairns, bases of awnings and "chenques" or funerary structures. Associated to one of these funerary structures, which is located at the top of Cerro Horqueta or Madre e Hija, human skeletal remains were recorded. In February of 2018, the structure was visited with the aim of obtaining a sample for radiocarbon dating and DNA analysis. The present work aims to generate bio-archaeological information, which is currently non-existent for the studied area. Specifically, we present here a bio anthropological analysis on a tooth recovered in the mentioned context. We determined it is a human, permanent upper left canine that belonged to an adolescent or young adult. The presence of a process of incipient hypercementosis, which can be interpreted as indicative of the use of the dentition for para-masticatory purposes, and the burial structure in which the tooth was found allow us to think that the individual may have belonged to an indigenous hunter-gatherer group.